An atypical phenotype of hypokalemic periodic paralysis caused by a mutation in the sodium channel gene - Yang Hee Park; June Bum Kim (Korean Pediatric Society, 2010)
Familial hypokalemic periodic paralysis is an autosomal-dominant channelopathy characterized by episodic muscle weakness with hypokalemia. The respiratory and cardiac muscles typically remain unaffected, but we report an atypical case of a family with hypokalemic periodic paralysis in which the affected members presented with frequent respiratory insufficiency during severe attacks. Molecular analysis revealed a heterozygous c.664 C>T transition in the sodium channel gene SCN4A, leading to an Arg222Trp mutation in the channel protein. The patients described here presented unusual clinical characteristics that included a severe respiratory phenotype, an incomplete penetrance in female carriers, and a different response to medications.